Dual Measurements of Pressure and Temperature With Fiber Bragg Grating Sensor - Mansour, Tahreer S.; Abdulhussein, Fahad M. (Al-Khwarizmi Engineering Journal, 2015)
Abstract The fiber Bragg grating (FBG) technology has been rapidly applied in the sensing technology field. In this work, uniform FBG was used as pressure sensor based on measuring related Bragg wavelength shift. The pressure was applied directly by air compressor to the sensor and the pressure was ranged from 1 to 6 bar. This sensor also was affected by the external temperature so as a result it could be used as a temperature sensor. This sensor could be used to monitor the pressure of dams. It has been shown from the result that the sensor is very sensitive to the pressure and the sensitivity was (67 pm) and is very sensitive to temperature and the sensitivity was (10pm oC). Keywords: fiber Bragg grating (FBG), fiber Bragg grating analyzer (FBGA), pressure sensor, Effective refractive index.